Preparation method and application of graphite negative electrode material for new energy battery
By pretreating natural graphite and using polyethylene glycol and surfactant with specific ratios, a uniform gel network structure is formed, which solves the problem of insufficient first discharge capacity and rate performance of graphite anode materials in lithium-ion batteries. It achieves stable capacity maintenance under different temperature conditions, improving the electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411404640.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The first discharge specific capacity of the graphite anode material of existing lithium-ion batteries is not ideal, and the rate performance and capacity retention rate are poor under different temperature conditions, resulting in insufficient electrochemical performance.
By pretreating natural graphite to increase the specific surface area and using specific ratios of polyethylene glycol and surfactant, a uniform gel network structure is formed, improving the dispersion of graphite powder and the retention of the cycle capacity of the battery. Specific steps include spark plasma discharge, stirring of the mixture, heating and evaporation, vacuum drying and calcining, ensuring uniform coating and stable electrolyte interface.
The first discharge specific capacity and rate performance of lithium batteries are improved, the circulation capacity retention rate at room temperature is improved, and the capacity is uniformly maintained under low and high temperature conditions is improved, improving the overall electrochemical performance of the battery.
Smart Images

Figure BDA0005076877860000101 
Figure BDA0005076877860000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to a preparation method and application of a graphite negative electrode material for new energy batteries. Background Art
[0002] With the progress of society and the growth of people's demand for energy, the greenhouse effect and environmental pollution caused by the use of traditional energy have become increasingly prominent, so the development and application of new energy sources are particularly urgent. As an energy technology that has been developed for many years, lithium-ion batteries have become a key research area in the academic community due to their environmental protection characteristics and low recycling costs.
[0003] The negative electrode is one of the core components of lithium-ion batteries. The battery's performance indicators such as capacity, charge and discharge rate, and service life depend largely on the selection of negative electrode materials. In order to improve the overall electrochemical performance of lithium-ion batteries, it is usually necessary to adjust and optimize the negative electrode material through modification.
[0004] Existing modification methods generally include: coating, blending, special morphology design, doping and other methods. In the prior art, the hard carbon coating method often uses hard carbon materials (such as polystyrene, etc.) and graphite materials to directly solidify and pyrolyze to achieve the coating of graphite materials, which requires long-term high-temperature stirring and it is difficult to ensure uniform coating. When uniform coating cannot be achieved, the rate performance will be significantly reduced. And the actual first discharge specific capacity of most lithium battery graphite negative electrode materials on the market currently does not exceed 350mAh / g. Therefore, the electrochemical properties of lithium battery graphite negative electrode materials, such as the first discharge specific capacity, need to be further improved.
[0005] Therefore, there is an urgent need for a preparation method and application of graphite negative electrode materials for new energy batteries. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a graphite negative electrode material for a new energy battery and its application.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a graphite negative electrode material for a new energy battery, the preparation method comprising the following steps:
[0009] (1) mixing natural graphite and water in a weight ratio of 1:(4-6), adding the mixture into a plasma reactor for spark plasma discharge, and obtaining pretreated graphite powder;
[0010] (2) Mixing polyethylene glycol, calcium chloride and water in a weight ratio of (3-6):1:(10-13), stirring evenly to obtain a mixed solution A; adding the pretreated graphite powder to the mixed solution A, continuing to add a surfactant, stirring for 4-6 hours, and obtaining a mixed solution B;
[0011] (3) heating the mixed solution B to 80-85° C. to evaporate until it becomes a gel-like substance, and vacuum drying the gel-like substance to obtain a precursor;
[0012] (4) calcining the precursor under a nitrogen atmosphere, and after calcination, crushing and sieving to obtain a graphite negative electrode material for new energy batteries.
[0013] Furthermore, in the step (1), the spark plasma discharge has a voltage of 10-15 KV, a current of 80-100 A, a pulse of 500-600 ns, a cumulative reaction time of 1-2 hours, and a reaction condition of a temperature of 80-100°C.
[0014] In the prior art, polymers are directly used to carbon-coat natural graphite. However, due to poor dispersion uniformity after mixing and uneven coating, the initial discharge capacity of the lithium-ion battery is not ideal. The present invention pre-treats natural graphite to improve the initial discharge capacity of the lithium-ion battery. The specific surface area of natural graphite can be increased by plasma discharge treatment, and the graphite powder surface is enriched with carboxyl, hydroxyl, epoxy and other groups, which can not only increase the specific surface area of graphite, but also improve its dispersibility. Under this condition, the initial charge and discharge efficiency of the battery is also improved.
[0015] Furthermore, the polyethylene glycol in step (2) is polyethylene glycol 400, polyethylene glycol 800 and polyethylene glycol 2000 in a weight ratio of 1: (1.2-1.5): (0.6-0.8).
[0016] The present invention prepares a precursor by combining polyethylene glycol with a specific ratio and pretreated graphite, which can improve the cycle capacity retention rate of lithium-ion batteries at room temperature. The analysis is that this is because PEGs with different molecular weights behave differently in the mixture: Polyethylene glycol 400 (PEG400): PEGs with lower molecular weights are easier to dissolve, have good fluidity, and help promote uniform mixing between other components; Polyethylene glycol 800 (PEG800) and Polyethylene glycol 2000 (PEG2000): PEGs with higher molecular weights have better film-forming properties, can provide structural support, and help form a stable gel network. When these PEGs with different molecular weights are mixed in a certain proportion, they can work together to provide good dispersibility and film-forming properties, thereby improving the cycle capacity retention rate of lithium-ion batteries at room temperature. However, the capacity retention rate of the battery at high and low temperatures is not ideal.
[0017] Furthermore, the weight of the surfactant in step (2) accounts for 1-2% of the weight of the pretreated graphite powder.
[0018] Furthermore, the surfactant in step (2) comprises a mixture of an alkyl glycoside (model: APG1214, purchased from Jinan Mingjiang Chemical Co., Ltd.), a polyoxyethylene fatty alcohol ether (AEO-9) and a polyoxyethylene ether nonionic surfactant in a weight ratio of (1.2-1.4):(0.3-0.6):1.
[0019] Furthermore, the preparation method of the polyoxyethylene ether nonionic surfactant in step (2) comprises the following steps:
[0020] (1) Under a nitrogen atmosphere, 60-70 parts by weight of a mixed monoalcohol and 2-5 parts by weight of KOH are mixed, the temperature is raised to 110-130° C., and then 30-40 parts by weight of ethylene oxide is added dropwise at a uniform rate for 1-2 hours. After the addition is completed, the mixture is kept warm for 1-2 hours at a pressure of 0.2-0.4 MPa and a temperature of 120-130° C. to obtain an oligomer polyether polyol;
[0021] (2) Under a nitrogen atmosphere, 70-80 parts by weight of oligomer polyether polyol, 20-30 parts by weight of mixed polyol and 2-4 parts by weight of catalase (purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number C6319) catalyst are added to a reactor, the temperature is raised to 140-145°C, and the pressure is increased to 0.3-0.4 MPa. When the pressure drops, the temperature is controlled at 110-115°C and the pressure is 0.3-0.4 MPa. The reaction is carried out for 2-3 hours to obtain a polyoxyethylene ether nonionic surfactant.
[0022] Furthermore, the mixed unit alcohol is a mixture of octanol, lauryl alcohol and isomeric tridecanol in a weight ratio of 1: (1.3-1.5): (0.6-0.8).
[0023] Furthermore, the mixed polyol is a mixture of glycerol, pentaerythritol and sorbitol in a weight ratio of (1.6-1.8):1:(0.3-0.5).
[0024] The present invention attempts to use commercially available surfactants to improve the uniformity of mixed solution B, but the effect is not ideal. The present invention can improve the capacity retention rate of the battery at low temperatures by mixing alkyl glycosides, polyoxyethylene fatty alcohol ethers and polyoxyethylene ether nonionic surfactants. And when alkyl glycosides, polyoxyethylene fatty alcohol ethers and polyoxyethylene ether nonionic surfactants are in specific ratios, the capacity retention rate at high temperatures is also improved. The surfactant under this condition can make the polymer and pretreated graphite better dispersed, ensuring that the uniform distribution and coating of the polymer and graphite particles are more uniform, thereby enhancing the contact between graphite and the electrolyte, and forming a more stable solid electrolyte interface (SEI) film.
[0025] Furthermore, in step (3), vacuum drying is performed at 60-65° C. for 25-30 h.
[0026] Furthermore, in the step (4), the sieving mesh number is 325 meshes.
[0027] Furthermore, the calcination conditions in step (4) are: calcination temperature is 1100-1200° C. for 2-3 hours.
[0028] The present invention also provides an application of a method for preparing a graphite negative electrode material for a new energy battery.
[0029] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0030] 1. The graphite negative electrode material prepared by the present invention can improve the initial discharge specific capacity of the lithium battery, has high rate performance and good high temperature resistance.
[0031] 2. The present invention pre-treats natural graphite to improve the initial discharge capacity of lithium-ion batteries and the initial charge and discharge efficiency of batteries.
[0032] 3. The precursor prepared by the present invention using polyethylene glycol in a specific ratio and pretreated graphite can improve the cycle capacity retention rate of lithium-ion batteries at room temperature.
[0033] 4. The present invention can improve the capacity retention rate of the battery at low temperature by mixing alkyl glycoside, polyoxyethylene fatty alcohol ether and polyoxyethylene ether nonionic surfactant. And when alkyl glycoside, polyoxyethylene fatty alcohol ether and polyoxyethylene ether nonionic surfactant are in a specific ratio, the capacity retention rate at high temperature is also improved. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The natural graphite used in the following examples has an average particle size of 20 μm and a particle size between 10 and 30 μm.
[0036] Example 1
[0037] This embodiment provides a method for preparing a graphite negative electrode material for a new energy battery, the preparation method comprising the following steps:
[0038] (1) Natural graphite and water are mixed in a weight ratio of 1:5, and added into a plasma reactor for spark plasma discharge, wherein the spark plasma discharge has a voltage of 12 KV, a current of 90 A, a pulse of 550 ns, a cumulative reaction time of 1.4 hours, and a reaction temperature of 90° C.; and pretreated graphite powder is obtained; the plasma reactor is a container having flat electrodes on both sides, a wire mesh at the bottom, and is insulated and sealed all around, with a capacity of 20 L, a distance between the flat electrodes of 20 cm, and a hole of the wire mesh of 1 mm.
[0039] (2) Mix polyethylene glycol, calcium chloride and water in a weight ratio of 5:1:12, stir evenly to obtain a mixed solution A; add the pretreated graphite powder to the mixed solution A, continue to add a surfactant, stir for 5 hours, and obtain a mixed solution B; the polyethylene glycol is polyethylene glycol 400, polyethylene glycol 800 and polyethylene glycol 2000 in a weight ratio of 1:1.4:0.7; the weight of the surfactant accounts for 1.5% of the weight of the pretreated graphite powder; the surfactant includes an alkyl glycoside (model: APG1214, purchased from Jinan Mingjiang Chemical Co., Ltd.), a polyoxyethylene fatty alcohol ether (AEO-9) and a polyoxyethylene ether nonionic surfactant in a weight ratio of 1.3:0.5:1;
[0040] The preparation method of polyoxyethylene ether nonionic surfactant comprises the following steps:
[0041] S1: Under a nitrogen atmosphere, 65 parts by weight of a mixed monoalcohol and 4 parts by weight of KOH were mixed, the temperature was raised to 120°C, and then 35 parts by weight of ethylene oxide were added dropwise at a uniform rate for 1.3 hours. After the addition was completed, the mixture was kept warm for 1.6 hours at a pressure of 0.3 MPa and a temperature of 125°C to obtain an oligomer polyether polyol; the mixed monoalcohol was a mixture of octanol, lauryl alcohol and isomeric tridecanol in a weight ratio of 1:1.4:0.7;
[0042] S2: Under a nitrogen atmosphere, 75 parts by weight of oligomer polyether polyol, 25 parts by weight of mixed polyol and 3 parts by weight of catalase (purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number C6319) catalyst are added to a reactor, wherein the mixed polyol is a mixture of glycerol, pentaerythritol and sorbitol in a weight ratio of 1.7:1:0.4; the temperature is raised to 142°C, and the pressure is increased to 0.35 MPa. When the pressure drops, the temperature is controlled at 112°C and the pressure is 0.35 MPa. The reaction is carried out for 2.6 hours to obtain a polyoxyethylene ether nonionic surfactant.
[0043] (3) heating the mixed solution B to 82° C. to evaporate until it becomes a gel-like substance, and vacuum drying the gel-like substance at 62° C. for 27 h to obtain a precursor;
[0044] (4) The precursor is calcined in a nitrogen atmosphere at a temperature of 1150° C. for 2.6 h. After the calcination is completed, the precursor is crushed and passed through a 325-mesh sieve to obtain a graphite negative electrode material for new energy batteries.
[0045] Example 2
[0046] This embodiment provides a method for preparing a graphite negative electrode material for a new energy battery, the preparation method comprising the following steps:
[0047] (1) Natural graphite and water are mixed in a weight ratio of 1:4, and added into a plasma reactor for spark plasma discharge, wherein the spark plasma discharge has a voltage of 10 KV, a current of 80 A, a pulse of 500 ns, a cumulative reaction time of 1 hour, and a reaction condition of a temperature of 80° C.; and pretreated graphite powder is obtained; the plasma reactor is a container having flat electrodes on both sides, a wire mesh at the bottom, and is insulated and sealed all around, with a capacity of 20 L, a distance between the flat electrodes of 20 cm, and a hole of the wire mesh of 1 mm.
[0048] (2) Mix polyethylene glycol, calcium chloride and water in a weight ratio of 3:1:10, stir evenly to obtain a mixed solution A; add the pretreated graphite powder to the mixed solution A, continue to add a surfactant, stir for 4 hours, and obtain a mixed solution B; the polyethylene glycol is polyethylene glycol 400, polyethylene glycol 800 and polyethylene glycol 2000 in a weight ratio of 1:1.2:0.6; the weight of the surfactant accounts for 1% of the weight of the pretreated graphite powder; the surfactant includes an alkyl glycoside (model: APG1214, purchased from Jinan Mingjiang Chemical Co., Ltd.) in a weight ratio of 1.2:0.3:1, a mixture of polyoxyethylene fatty alcohol ether (AEO-9) and a polyoxyethylene ether nonionic surfactant;
[0049] The preparation method of polyoxyethylene ether nonionic surfactant comprises the following steps:
[0050] S1: Under a nitrogen atmosphere, 60 parts by weight of a mixed monoalcohol and 2 parts by weight of KOH are mixed, the temperature is raised to 110°C, and then 40 parts by weight of ethylene oxide are added dropwise at a uniform rate for 1 hour. After the addition is completed, the mixture is kept warm for 1 hour at a pressure of 0.2 MPa and a temperature of 120°C to obtain an oligomer polyether polyol; the mixed monoalcohol is a mixture of octanol, lauryl alcohol and isomeric tridecanol in a weight ratio of 1:1.3:0.6;
[0051] S2: Under a nitrogen atmosphere, 70 parts by weight of oligomer polyether polyol, 30 parts by weight of mixed polyol and 2 parts by weight of catalase (purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number C6319) catalyst are added to a reactor, wherein the mixed polyol is a mixture of glycerol, pentaerythritol and sorbitol in a weight ratio of 1.6:1:0.3; the temperature is raised to 140°C, and the pressure is increased to 0.3 MPa. When the pressure drops, the temperature is controlled at 110°C and the pressure is 0.3 MPa. The reaction is carried out for 2 hours to obtain a polyoxyethylene ether nonionic surfactant.
[0052] (3) heating the mixed solution B to 80° C. to evaporate until it becomes a gel-like substance, and vacuum drying the gel-like substance at 60° C. for 25 h to obtain a precursor;
[0053] (4) The precursor is calcined in a nitrogen atmosphere at a temperature of 1100° C. for 2 h. After the calcination is completed, the precursor is crushed and passed through a 325-mesh sieve to obtain a graphite negative electrode material for new energy batteries.
[0054] Example 3
[0055] This embodiment provides a method for preparing a graphite negative electrode material for a new energy battery, the preparation method comprising the following steps:
[0056] (1) Natural graphite and water are mixed in a weight ratio of 1:6, and added into a plasma reactor for spark plasma discharge, wherein the spark plasma discharge has a voltage of 15 KV, a current of 100 A, a pulse of 600 ns, a cumulative reaction time of 2 hours, and a reaction condition of a temperature of 100° C.; and pretreated graphite powder is obtained; the plasma reactor is a container having flat electrodes on both sides, a wire mesh at the bottom, and an insulated and closed container on all sides, with a capacity of 20 L, a distance between the flat electrodes of 20 cm, and a hole of the wire mesh of 1 mm.
[0057] (2) Mix polyethylene glycol, calcium chloride and water in a weight ratio of 6:1:13, stir evenly to obtain a mixed solution A; add the pretreated graphite powder to the mixed solution A, continue to add a surfactant, stir for 6 hours, and obtain a mixed solution B; the polyethylene glycol is polyethylene glycol 400, polyethylene glycol 800 and polyethylene glycol 2000 in a weight ratio of 1:1.5:0.8; the weight of the surfactant accounts for 2% of the weight of the pretreated graphite powder; the surfactant includes an alkyl glycoside (model: APG1214, purchased from Jinan Mingjiang Chemical Co., Ltd.) in a weight ratio of 1.4:0.6:1, a mixture of polyoxyethylene fatty alcohol ether (AEO-9) and a polyoxyethylene ether nonionic surfactant;
[0058] The preparation method of polyoxyethylene ether nonionic surfactant comprises the following steps:
[0059] S1: Under a nitrogen atmosphere, 70 parts by weight of a mixed monoalcohol and 5 parts by weight of KOH are mixed, the temperature is raised to 130°C, and then 30 parts by weight of ethylene oxide are added dropwise at a uniform rate for 2 hours. After the addition is completed, the mixture is kept warm for 2 hours at a pressure of 0.4 MPa and a temperature of 130°C to obtain an oligomer polyether polyol; the mixed monoalcohol is a mixture of octanol, lauryl alcohol and isomeric tridecanol in a weight ratio of 1:1.5:0.8;
[0060] S2: Under a nitrogen atmosphere, 80 parts by weight of oligomer polyether polyol, 20 parts by weight of mixed polyol and 4 parts by weight of catalase (purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number C6319) catalyst are added to a reactor, wherein the mixed polyol is a mixture of glycerol, pentaerythritol and sorbitol in a weight ratio of 1.8:1:0.5; the temperature is raised to 145°C, and the pressure is increased to 0.4 MPa. When the pressure drops, the temperature is controlled at 115°C and the pressure is 0.4 MPa. The reaction is carried out for 3 hours to obtain a polyoxyethylene ether nonionic surfactant.
[0061] (3) heating the mixed solution B to 85° C. to evaporate until it becomes a gel-like substance, and vacuum drying the gel-like substance at 65° C. for 30 h to obtain a precursor;
[0062] (4) The precursor is calcined in a nitrogen atmosphere at a temperature of 1200° C. for 3 h. After the calcination is completed, the precursor is crushed and passed through a 325-mesh sieve to obtain a graphite negative electrode material for new energy batteries.
[0063] Comparative Example 1
[0064] The difference between this comparative example and Example 1 is that the preparation method of the pretreated graphite powder is different.
[0065] Specifically, natural graphite is placed in a muffle furnace and calcined at 800° C. for 1.5 hours to obtain pretreated graphite powder.
[0066] Comparative Example 2
[0067] The difference between this comparative example and Example 1 is that the spark plasma discharge voltage is 8 KV, the current is 120 A, the pulse is 400 ns, the cumulative reaction time is 2.4 hours, and the reaction condition is a temperature of 70°C.
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that the polyethylene glycol is polyethylene glycol 400, polyethylene glycol 800 and polyethylene glycol 2000 in a weight ratio of 1:1:1.
[0070] Comparative Example 4
[0071] The difference between this comparative example and Example 1 is that the surfactant comprises a mixture of alkyl glycoside, polyoxyethylene fatty alcohol ether and polyoxyethylene ether nonionic surfactant in a weight ratio of 1:1:1.
[0072] Comparative Example 5
[0073] The difference between this comparative example and Example 1 is that the surfactant includes a mixture of alkyl glycoside (model: APG1214, purchased from Jinan Mingjiang Chemical Co., Ltd.), polyoxyethylene fatty alcohol ether (AEO-9) and Tween 60 in a weight ratio of 1.3:0.5:1.
[0074] Comparative Example 6
[0075] The difference between this comparative example and Example 1 is that the mixed monoalcohol is a mixture of octanol, lauryl alcohol and isomeric tridecanol in a weight ratio of 1:1:1; the mixed polyol is a mixture of glycerol, pentaerythritol and sorbitol in a weight ratio of 1:1:1.
[0076] Performance Testing
[0077] Semi-electric test method: The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-6: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1:1.5:2.5 were mixed evenly and applied on copper foil. The coated electrode was placed in a vacuum drying oven at 120°C and dried for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon gas. The electrolyte was 1M-LiPF6+EC:DEC:DMC=1:1:1 (volume ratio). The metal lithium sheet was the counter electrode. The simulated battery test was carried out in a 5V-10mA Xinwei battery test cabinet. The charge and discharge voltage was 0.01-1.5V, and the charge and discharge rate was 0.1C. The first capacity and efficiency obtained by the test are listed in Table 1.
[0078] Full battery test method: The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-6 are used as the negative electrode, lithium cobalt oxide is used as the positive electrode, and 1M-LiPF6+EC:DEC:DMC=1:1:1 (volume ratio) solution is used as the electrolyte to assemble a full battery, and the battery is charged and discharged at room temperature, 45°C, and -10°C at a rate of 1C. The voltage range is 3.0-4.2V, and the cycle performance obtained from the test is listed in Table 1.
[0079] The specific test results are shown in Table 1.
[0080] Table 1 Electrochemical performance test results
[0081]
[0082]
[0083] It can be seen from the above performance test results that the lithium batteries prepared with the negative electrode materials of Examples 1-3 have excellent performance, especially the comprehensive performance of Example 1 is the most outstanding.
[0084] However, the comparative examples were significantly inferior to the embodiments in corresponding performance tests because they did not adopt the necessary technical solutions. In comparative example 1, the pretreatment method of natural graphite was changed, resulting in a decrease in the initial discharge capacity of the lithium-ion battery; in comparative example 2, the spark plasma discharge conditions were changed, which affected the group distribution on the surface of the pretreated graphite, further affecting the initial discharge capacity of the lithium-ion battery; in comparative example 3, the proportion of polyethylene glycol was changed, and the cycle capacity retention rate of the lithium-ion battery at room temperature decreased; in comparative examples 4-6, the surfactant composition was changed, and the capacity retention rate of the battery at high and low temperatures was improved. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0085] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a graphite negative electrode material for a new energy battery, characterized in that: The preparation method comprises the following steps: (1) mixing natural graphite and water in a weight ratio of 1:(4-6), adding the mixture into a plasma reactor for spark plasma discharge, and obtaining pretreated graphite powder; (2) Mixing polyethylene glycol, calcium chloride and water in a weight ratio of (3-6):1:(10-13), stirring evenly to obtain a mixed solution A; adding the pretreated graphite powder to the mixed solution A, continuing to add a surfactant, stirring for 4-6 hours, and obtaining a mixed solution B; (3) heating the mixed solution B to 80-85° C. to evaporate until it becomes a gel-like substance, and vacuum drying the gel-like substance to obtain a precursor; (4) calcining the precursor under a nitrogen atmosphere, and after calcination, crushing and sieving to obtain a graphite negative electrode material for new energy batteries.
2. The method for preparing a graphite negative electrode material for a new energy battery according to claim 1, characterized in that: In the step (1), the spark plasma discharge has a voltage of 10-15 KV, a current of 80-100 A, a pulse of 500-600 ns, a cumulative reaction time of 1-2 hours, and a reaction condition of a temperature of 80-100° C.
3. The method for preparing a graphite negative electrode material for a new energy battery according to claim 1, characterized in that: The polyethylene glycol in step (2) is polyethylene glycol 400, polyethylene glycol 800 and polyethylene glycol 2000 in a weight ratio of 1: (1.2-1.5): (0.6-0.8).
4. The method for preparing a graphite negative electrode material for a new energy battery according to claim 1, characterized in that: The weight of the surfactant in step (2) accounts for 1-2% of the weight of the pretreated graphite powder.
5. The method for preparing a graphite negative electrode material for a new energy battery according to claim 1, characterized in that: The surfactant in step (2) comprises a mixture of alkyl glycoside, polyoxyethylene fatty alcohol ether and polyoxyethylene ether nonionic surfactant in a weight ratio of (1.2-1.4): (0.3-0.6):
1.
6. The method for preparing a graphite negative electrode material for a new energy battery according to claim 1, characterized in that: The preparation method of the polyoxyethylene ether nonionic surfactant in step (2) comprises the following steps: (1) Under a nitrogen atmosphere, 60-70 parts by weight of a mixed monoalcohol and 2-5 parts by weight of KOH are mixed, the temperature is raised to 110-130° C., and then 30-40 parts by weight of ethylene oxide is added dropwise at a uniform rate for 1-2 hours. After the addition is completed, the mixture is kept warm for 1-2 hours at a pressure of 0.2-0.4 MPa and a temperature of 120-130° C. to obtain an oligomer polyether polyol; (2) Under a nitrogen atmosphere, 70-80 parts by weight of oligomer polyether polyol, 20-30 parts by weight of mixed polyol and 2-4 parts by weight of catalase catalyst are added to a reactor, the temperature is raised to 140-145° C., and the pressure is increased to 0.3-0.4 MPa. When the pressure drops, the temperature is controlled to 110-115° C. and the pressure is controlled to 0.3-0.4 MPa. The reaction is carried out for 2-3 hours to obtain a polyoxyethylene ether nonionic surfactant.
7. The method for preparing a graphite negative electrode material for a new energy battery according to claim 6, characterized in that: The mixed unit alcohol is a mixture of octanol, lauryl alcohol and isomeric tridecanol in a weight ratio of 1: (1.3-1.5): (0.6-0.8).
8. The method for preparing a graphite negative electrode material for a new energy battery according to claim 6, characterized in that: The mixed polyol is a mixture of glycerol, pentaerythritol and sorbitol in a weight ratio of (1.6-1.8):1:(0.3-0.5).
9. The method for preparing a graphite negative electrode material for a new energy battery according to claim 1, characterized in that: The calcination conditions in step (4) are: calcination at a temperature of 1100-1200° C. for 2-3 hours.
10. An application of the method for preparing a graphite negative electrode material for new energy batteries according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing micron graphite powder by using spark plasma
CN102674322A
Preparation method of low specific surface area carbon / carbon composite cathode material of lithium ion battery
CN104766961A
Dielectric barrier discharge plasma purification method for graphite
CN111422863A
Negative electrode material for lithium ion battery and preparation method of negative electrode material
CN114249324A
High-rate regenerated graphite negative electrode material as well as preparation method and application thereof
CN118198570A
